Process for the production of mesitylene
Patent Information
- Application Number
- CN202510491128.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2026-10-23
AI Technical Summary
这些液体酸活性较高,但腐蚀性较强,需要使用耐腐蚀的容器,以及液体酸潜在的安全和环保问题、以及酸溶油的高昂的处理价格都提高了生产成本
[0009]本发明提供的方法,通过采用特定种类的固体催化剂,控制催化剂中强酸和强酸酸量的占比,二者在特定范围内,能够有效的提高目标产物选择性和催化剂寿命,有利于减少副反应的发生,该方法能够实现均三甲基苯胺的绿色合成,在保证催化剂寿命的同时提高目标产物的选择性。
Smart Images

Figure BDA0005365617900000121 
Figure BDA0005365617900000131 
Figure BDA0005365617900000141
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of preparing mesitylene, and more specifically to a method for producing mesitylene. Background Technology
[0002] Trimethylaniline is an important organic synthesis intermediate with a variety of applications, mainly including the following:
[0003] In some organic reactions, mesitylene can act as a catalyst, promoting the reaction process. For example, in certain coupling reactions, it can undergo cross-coupling reactions with aryl halides under transition metal catalysis, used in the preparation of diphenylamine derivatives. As a solvent: Due to its good solubility, it can dissolve in organic solvents such as alcohols and ethers, and is therefore often used as a solvent in organic synthesis, providing a suitable medium environment for the reaction. Mesitylene is an important intermediate in the synthesis of many dyes and organic pigments. In dye industry production, it can be used to prepare various types of dyes, such as acid dyes, basic dyes, and disperse dyes, and is widely used in dyeing and coloring processes in the textile, paper, and plastics industries. In the pesticide field, mesitylene can be used to synthesize some pesticide intermediates, which are then used in the production of insecticides, herbicides, and other pesticide products, playing an important role in the control of pests and diseases in agricultural production. In pharmaceutical synthesis, mesitylene can also serve as an intermediate for certain drugs, participating in the drug synthesis process and providing important raw material support for the pharmaceutical industry. In the rubber processing process, mesitylene trimethylaniline can be used to prepare some rubber additives, such as antioxidants, which help improve the performance and service life of rubber products.
[0004] There are generally two traditional methods for synthesizing mesitylene: the earliest industrial method for producing mesitylene involved two steps. The first step was to nitrate mesitylene with nitrosulfuric acid. The second step was to reduce hydrogenated nitro-mesitylene via a reaction. The disadvantage of this method is the generation of a large amount of waste. In the nitration stage, producing 1 ton of nitro-mesitylene with a yield of 92% generates a mixed wastewater of sulfuric acid, nitric acid, and acetic acid. In the reduction stage, producing 1 ton of mesitylene with a yield of 87% generates 69.4 tons of liquid, including 30.74 tons of unusable sludge and 1 ton of solid waste.
[0005] In recent years, another process has been developed to produce mesitylene from o-toluidine and methanol in the presence of a catalyst. However, the mainstream catalysts currently used are liquid acids such as sulfuric acid and trifluoromethanesulfonic acid. These liquid acids are highly reactive but also highly corrosive, requiring the use of corrosion-resistant containers. Furthermore, the potential safety and environmental issues associated with liquid acids, as well as the high cost of treating acid-soluble oils, all increase production costs. Therefore, the production of mesitylene requires the search for new green catalysts. Developing novel and efficient catalysts to achieve the green synthesis of mesitylene is currently a hot research topic and a challenge. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems existing in the prior art and provide a method for producing mesitylene trimethylaniline. This method enables the green synthesis of mesitylene trimethylaniline and improves the selectivity of the target product.
[0007] To achieve the above objectives, the present invention provides a method for producing mesitylenetrimethylaniline, wherein the method comprises: reacting o-toluidine and a methylating agent in the presence of a catalyst at a reaction temperature not lower than 380°C;
[0008] The catalyst comprises a molecular sieve, an oxide binder, and a modifying component. The modifying component is loaded on both the molecular sieve and the oxide binder. The modifying component contains Cu and P. The percentage of the medium-strong acid in the catalyst is not less than 40% of the total acid content, and the percentage of the strong acid in the catalyst is not less than 30% of the total acid content. The percentage of the medium-strong acid in the total acid content is calculated as the percentage of the desorption peak area at 250℃-450℃ measured using the NH3 temperature-programmed desorption method to the total acid desorption peak area. The percentage of the strong acid in the total acid content is calculated as the percentage of the desorption peak area at 450℃-550℃ measured using the NH3 temperature-programmed desorption method to the total acid desorption peak area.
[0009] The method provided by this invention, by employing a specific type of solid catalyst and controlling the ratio of strong acid and strong acid content in the catalyst, within a specific range, can effectively improve the selectivity of the target product and the catalyst lifetime, and help reduce the occurrence of side reactions. This method can realize the green synthesis of mesitylene, and improve the selectivity of the target product while ensuring the catalyst lifetime. Detailed Implementation
[0010] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0011] This invention provides a method for producing mesitylenetrimethylaniline, wherein the method comprises: reacting o-toluidine and a methylating agent in the presence of a catalyst at a reaction temperature not lower than 380°C;
[0012] The catalyst comprises a molecular sieve, an oxide binder, and a modifying component. The modifying component is loaded on both the molecular sieve and the oxide binder. The modifying component contains Cu and P. The percentage of the medium-strong acid in the catalyst is not less than 40% of the total acid content, and the percentage of the strong acid in the catalyst is not less than 30% of the total acid content. The percentage of the medium-strong acid in the total acid content is calculated as the percentage of the desorption peak area at 250℃-450℃ measured using the NH3 temperature-programmed desorption method to the total acid desorption peak area. The percentage of the strong acid in the total acid content is calculated as the percentage of the desorption peak area at 450℃-550℃ measured using the NH3 temperature-programmed desorption method to the total acid desorption peak area.
[0013] The method provided by this invention, by employing a specific type of solid catalyst and controlling the ratio of strong acid and strong acid content in the catalyst, helps to reduce the occurrence of side reactions. This method can achieve the green synthesis of mesitylene and improve the selectivity of the target product.
[0014] In this invention, the acid content distribution of the catalyst was characterized using the NH3 temperature-programmed desorption method (NH3-TPD). The characterization method is as follows: Instrument: Quantachrome Chemstar TPx; Test procedure: 0.15 g (20-40 mesh) of molecular sieve or catalyst sample was weighed, heated to 550 °C to dry, and then cooled to 100 °C to saturate the catalyst with NH3 adsorption. The temperature was then raised to 250 °C, 350 °C, 450 °C, and 550 °C to desorb NH3, and the NH3 concentration was detected using a TCD detector. The adsorption curves obtained at different temperature ranges were integrated, and the instrument automatically calculated the acid density distribution at different temperatures. Among them, the acid content obtained by integration at 150 °C-250 °C is weak acid, 250 °C-450 °C is medium-strong acid, and 450 °C-550 °C is strong acid; the total acid content is obtained at 150 °C-550 °C.
[0015] In this invention, the type of methylating agent is not particularly limited. Preferably, the methylating agent is formic acid and / or methanol.
[0016] In this invention, preferably, the molar ratio of the reaction raw material to the methylating agent is 2-20:1, more preferably 2.5-8:1.
[0017] In this invention, preferably, the reaction conditions include: a reaction temperature of 380-480°C, and a mass hourly space velocity (HHSV) of 0.1-5 h⁻¹ for the o-toluidine and the methylating reagent. -1 Preferably, the reaction conditions include: a reaction temperature of 380-450°C, and a mass hourly space velocity (HHSV) of 0.1-2 h⁻¹ for the o-toluidine and the methylating reagent. -1 .
[0018] In this invention, preferably, the reaction is a gas-phase reaction.
[0019] In this invention, it should be noted that the gas-phase reaction refers to the fact that both the reactants and the methylating reagent are fed in the gas phase or that the reaction conditions during the reaction process cause the reactants and the methylating reagent to be in the gas phase. This invention does not have a particular limitation on the gasification method, and the gasification methods conventionally defined in the art can be applied to this invention.
[0020] In this invention, preferably, the method is carried out in at least one of a fixed-bed reactor, a fluidized-bed reactor, a moving-bed reactor, and a slurry-bed reactor, and more preferably in a fixed-bed reactor.
[0021] In this invention, preferably, the percentage of the medium-strong acid content in the catalyst relative to the total acid content is 42-47%, and this percentage is expressed as the percentage of the desorption peak area at 250°C-450°C measured using the NH3 temperature-programmed desorption method relative to the total acid desorption peak area. For example, the percentage of the medium-strong acid content in the catalyst relative to the total acid content can be 42%, 43%, 44%, 45%, 46%, 47%, or even higher, or can be within a range consisting of any two of the above values.
[0022] In this invention, preferably, the strong acid content of the catalyst accounts for 30-36% of the total acid content, and the medium strong acid content accounts for the percentage of the total acid content as the percentage of the desorption peak area at 450℃-550℃ measured by the NH3 temperature-programmed desorption method to the total acid desorption peak area.
[0023] The catalyst of this invention has a high ratio of medium-strong acid to strong acid, which has the advantage of improving the selectivity of the target product mesitylene.
[0024] In this invention, preferably, the molecular sieve is selected from at least one of Y-type molecular sieves, ZSM-5 type molecular sieves, β-type molecular sieves, MCM-22 type molecular sieves, and mordenite type molecular sieves, more preferably from at least one of Y-type molecular sieves, ZSM-5 type molecular sieves, and β-type molecular sieves, and more preferably from β-type molecular sieves. When β-type molecular sieves are used to produce mesitylene, they exhibit high reactant conversion and high target product selectivity, and also have an extended catalyst lifetime.
[0025] In this invention, preferably, the oxide binder is alumina and / or silicon oxide. By simultaneously modifying both the molecular sieve and the oxide binder, this invention further increases the proportion of medium-strong acids in the catalyst, thereby improving the catalyst's stability, catalytic performance, and lifespan.
[0026] In this invention, preferably, the Cu:P molar ratio in the catalyst is 1:0.1-10, more preferably 1:0.2-0.5, wherein Cu is calculated as CuO and P is calculated as P2O5.
[0027] In this invention, preferably, the mass ratio of the molecular sieve to the oxide binder (calculated as oxide) is 95:5-20:80, more preferably 90:10-25:75.
[0028] In this invention, preferably, the mass ratio of the oxide binder (calculated as oxide) to the copper (calculated as element) is 75:25-99:1, more preferably 90:10-98:2.
[0029] In this invention, the content of molecular sieve and oxide binder in the catalyst is calculated by the amount of feed.
[0030] In this invention, the copper and phosphorus contents in the catalyst were determined by X-ray fluorescence (XRF) under the following conditions: tungsten target (excitation voltage 40 kV, excitation current 250 mA). The sample powder was pressed into tablets, with an applied pressure typically of 500-1000 kPa. The relationship between the fluorescence wavelength and the atomic number Z of the element follows Moseley's law: λ = K(ZS). -2 Based on this, qualitative analysis of elements is performed by measuring fluorescence wavelengths. Semi-quantitative analysis of elements is performed by utilizing the relationship that the intensity of each element's fluorescence rays is proportional to its concentration.
[0031] In this invention, the preparation method of the catalyst is not particularly limited. According to one specific embodiment of the present invention, the preparation method of the catalyst includes:
[0032] (1) Mix the molecular sieve and oxide binder to obtain a mixture;
[0033] (2) The mixture obtained in step (1) is mixed with a solution containing copper precursor and phosphorus compound and then calcined once.
[0034] The method provided by this invention controls the order of adding raw materials during catalyst preparation. It strictly follows the procedure of first mixing the molecular sieve and the support, and then directly mixing them with a solution containing a copper precursor and a phosphorus compound to form the catalyst without calcination. The catalyst preparation process only requires one calcination, avoiding the multiple calcinations required for modification after catalyst formation in the prior art, thus reducing the difficulty of the catalyst preparation process and reducing energy consumption.
[0035] In this invention, the types of oxide binders used in step (1) have been described above and will not be repeated here.
[0036] In this invention, the range of suitable amounts for the molecular sieve and oxide binder is relatively wide. Preferably, in step (1), the amount of molecular sieve and oxide binder is such that the mass ratio of the molecular sieve to the oxide binder (calculated as oxide) in the prepared catalyst is 95:5-20:80, more preferably 90:10-25:75.
[0037] In this invention, the performance of the catalyst is improved by controlling the form in which the oxide binder exists. Preferably, in step (1), the oxide binder is a solid oxide binder and / or a sol-gel oxide binder, more preferably a sol-gel oxide binder. The advantage of this preferred embodiment is that the molecular sieve and the oxide binder can be mixed better, distributed more uniformly, and have stronger interactions, resulting in better catalyst activity and stability.
[0038] In this invention, preferably, when the oxide binder is a sol-gel oxide binder, the oxide binder is provided by aluminum sol and / or silica sol.
[0039] In this invention, the concentration of the colloidal oxide binder is not particularly limited. Preferably, the concentration of each colloidal oxide binder is 0.1-50 wt%, more preferably 10-30 wt%.
[0040] In this invention, preferably, the pH of the sol-oxide binder is 1-5.
[0041] In this invention, preferably, the average particle size of the sol-oxide binder is 0.1-300 nm.
[0042] In this invention, preferably, in step (1), the oxide binder is aluminum oxide.
[0043] In this invention, there is no particular limitation on the type of alumina precursor; any substance conventionally defined in the art that can be converted into alumina by calcination is applicable to this invention. Preferably, the alumina is provided by at least one of boehmite, aluminum chloride, aluminum hydroxide, and aluminum sol.
[0044] In this invention, the types of molecular sieves used in step (1) have been described above and will not be repeated here.
[0045] In this invention, preferably, in step (1), the silicon-aluminum molar ratio n(SiO2):n(Al2O3) of the molecular sieve is 2-1000:1, more preferably 2-100:1.
[0046] In this invention, preferably, in step (1), the average particle size of the molecular sieve is 0.01-50 μm, more preferably 0.1-20 μm.
[0047] In this invention, there is no particular limitation on the type of copper precursor, as long as copper can be provided. Preferably, in step (2), the copper precursor is selected from copper-soluble compounds, and more preferably from at least one of copper chloride, cuprous chloride, copper nitrate, copper sulfate, and cuprous sulfate.
[0048] In this invention, there is no particular limitation on the type of phosphorus-containing compound, as long as it can provide phosphorus. Preferably, in step (2), the phosphorus-containing compound is selected from at least one of phosphoric acid, phosphorous acid, soluble phosphate, and phosphite.
[0049] In this invention, there is no particular limitation on the specific type of soluble phosphate. Preferably, the soluble phosphate is selected from at least one of ammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
[0050] In this invention, preferably, the phosphorus-containing compound is provided by an aqueous solution of the phosphorus-containing compound. Preferably, the concentration of the aqueous solution of the phosphorus-containing compound is 0.01-25 wt%, more preferably 5-25 wt%.
[0051] In this invention, there is no particular limitation on the amount of copper precursor and phosphorus precursor used. Preferably, in step (2), the amount of copper precursor and phosphorus precursor used is such that the Cu:P molar ratio in the prepared catalyst is 1:0.1-10, preferably 1:0.2-0.5, wherein Cu is calculated as CuO and P is calculated as P2O5. By controlling the amount of copper precursor and phosphorus-containing compound, the acid distribution in the catalyst can be controlled, the proportion of medium-strong acid can be increased, and the hydrothermal stability of the catalyst can be improved, enabling long-term continuous operation of the catalyst, which is beneficial to industrial production.
[0052] In this invention, preferably, the amount of copper precursor and oxide binder is such that the mass ratio of the oxide binder (calculated as oxide) to the copper precursor (calculated as element) in the prepared catalyst is 75:25-99:1, preferably 90:10-98:2.
[0053] In this invention, when the oxide binder is a sol-gel oxide binder, a peptizing solvent needs to be introduced to dissolve it. This invention does not particularly limit the specific operation method of dissolving the adhesive, and those skilled in the art can choose according to actual needs. Preferably, step (2) further includes: introducing a peptizing solvent into a solution containing a copper precursor and a phosphorus-containing compound and mixing it with the mixture obtained in step (1) to form a mold.
[0054] In this invention, there is no particular limitation on the type of adhesive solvent; adhesive solvents conventionally defined in the art are applicable to this invention. Preferably, the adhesive solvent is selected from at least one of nitric acid, hydrochloric acid, sulfuric acid, formic acid, and acetic acid.
[0055] In this invention, there is no particular limitation on the amount of peptizing solvent used, as long as it meets the peptizing requirements. Those skilled in the art can select the appropriate amount based on actual needs. Preferably, the amount of peptizing solvent is such that the pH of the solution containing the copper precursor and the phosphorus-containing compound is 1-4. Similarly, this invention does not particularly limit the concentration of the peptizing solvent; those skilled in the art can select the appropriate concentration based on actual needs.
[0056] In this invention, there is no particular limitation on the molding method in step (2). Those skilled in the art can choose according to actual needs, such as ball forming, sheet forming, extrusion forming, etc.
[0057] In this invention, the range of roasting conditions is relatively wide. Preferably, in step (2), the roasting conditions include: a temperature of 450-800℃ and a time of 1-15h; more preferably, in step (2), the roasting conditions include: a temperature of 500-700℃ and a time of 2-8h.
[0058] The present invention will be described in detail below through preparation examples and embodiments.
[0059] Unless otherwise specified, all raw materials used in the following preparation examples and embodiments are commercially available. The molecular sieves and oxide binders were purchased from Sinopec Catalyst Branch.
[0060] In the following examples and comparative examples, the conversion rate of the reactants and the selective distribution of the resulting products were determined by an Anglient-7890 gas chromatograph equipped with a high-pressure sampler (HP-PONA 50m × 0.2mm capillary column). The detection method for determining the catalyst single-pass lifetime was as follows: the catalyst was considered deactivated when the conversion rate of the reactants decreased to 90%, and the reaction time experienced by the catalyst was the catalyst single-pass lifetime.
[0061] In this invention, the acid content distribution of the catalyst was characterized using the NH3 temperature-programmed desorption method (NH3-TPD). The characterization method is as follows: Instrument: Quantachrome Chemstar TPx; Testing procedure: 0.15 g (20-40 mesh) of catalyst sample was weighed, heated to 550 °C to dry, and then cooled to 100 °C to saturate the catalyst with NH3 adsorption. The temperature was then raised to 250 °C, 350 °C, 450 °C, and 550 °C to desorb NH3, and the NH3 concentration was detected using a TCD detector. The adsorption curves obtained at different temperature ranges were integrated, and the instrument automatically calculated the acid density distribution at different temperatures. The acid content obtained at 250 °C was identified as a weak acid, 250 °C-450 °C as a medium-strong acid, and 450 °C-550 °C as a strong acid.
[0062] Preparation examples are used to illustrate the preparation of catalysts.
[0063] Preparation Example 1
[0064] (1) Mix 85g of HY molecular sieve (silicon-aluminum molar ratio n(SiO2):n(Al2O3) is 5, average particle size is 1μm) and 15g of alumina (average particle size is 20μm) evenly;
[0065] (2) Add 1.5g of cuprous chloride to 100g of H3PO4 solution with a concentration of 10wt%, and then add it to the mixture in step (1). After mixing evenly, extrude it using an extruder and calcine it at 500℃ for 12h to obtain catalyst Y-1.
[0066] Preparation Example 2
[0067] (1) Mix 750g of β molecular sieve (silicon-aluminum molar ratio n(SiO2):n(Al2O3) is 20, average particle size is 1.5μm) and 1250g of aluminum sol with a concentration of 20wt% (average particle size is 10nm) evenly.
[0068] (2) Add 30g Cu2SO4 to 100g KH2PO4 solution with a concentration of 30wt%, then adjust the pH to 2.5 with nitric acid and add it to the mixture in step (1). After mixing evenly, extrude the mixture using an extruder and calcine it at 600℃ for 1h to obtain catalyst β-1.
[0069] Preparation Example 3
[0070] (1) 200g of ZSM-5 molecular sieve (silicon-aluminum molar ratio n(SiO2):n(Al2O3) is 50, average particle size is 0.5μm) and 500g of silica sol with a concentration of 20wt% (average particle size is 20nm) are mixed evenly.
[0071] (2) Add 10g Cu(NO3)2 to 250g K3PO4 solution with a concentration of 20wt%, add it to the mixture in step (1), mix evenly, and then extrude it into shape using an extruder. Calcine it at 800℃ for 2h to obtain catalyst ZSM-1.
[0072] Preparation Example 4
[0073] The catalyst was prepared according to the method of Preparation Example 2, except that in step (2), 20g of Cu2SO4 was added to 200g of KH2PO4 solution with a concentration of 10wt%, and then the pH was adjusted to 4 with nitric acid before being added to the mixture in step (1). The mixture was then calcined at 500°C for 8 hours to obtain catalyst β-2.
[0074] Preparation Example 5
[0075] The catalyst was prepared according to the method of Preparation Example 2, except that in step (2), 50g of Cu2SO4 was added to 500g of KH2PO4 solution with a concentration of 10wt%, and other conditions remained unchanged, to obtain catalyst β-3.
[0076] Preparation Example 6
[0077] The catalyst was prepared according to the method of Preparation Example 2, except that in step (2), 10g of Cu2SO4 was added to 200g of KH2PO4 solution with a concentration of 10wt%, and other conditions remained unchanged, to obtain catalyst β-4.
[0078] Preparation Example 7
[0079] The catalyst was prepared according to the method of Preparation Example 2, except that in step (1), alumina powder (average particle size of 20 μm) was used instead of aluminum sol, and other conditions remained unchanged, to obtain catalyst β-5.
[0080] Preparation of Comparative Example 1
[0081] The catalyst was prepared according to the method of Preparation Example 1, except that in step (2), a copper salt solution without phosphoric acid (100g of CuCl solution with a concentration of 8wt%) was added, and other conditions remained unchanged, to obtain catalyst DY-1.
[0082] Preparation of Comparative Example 2
[0083] The catalyst was prepared according to the method of Preparation Example 1, except that in step (2), a phosphoric acid solution without copper salt (100g of H3PO4 solution with a concentration of 15wt%) was added, and other conditions remained unchanged, to obtain catalyst DY-2.
[0084] Preparation of Comparative Example 3
[0085] The catalyst was prepared according to the method of Preparation Example 2, except that in step (2), 20g of Cu2SO4 was added to 200g of KH2PO4 solution with a concentration of 20wt%, and other conditions remained unchanged, thus obtaining catalyst Dβ-1.
[0086] Preparation of Comparative Example 4
[0087] The catalyst was prepared according to the method of Preparation Example 2, except that in step (2), a phosphate solution without copper salt (200g of KH2PO4 solution with a concentration of 5wt%) was added to obtain catalyst Dβ-2.
[0088] Preparation of Comparative Example 5
[0089] The catalyst was prepared according to the method of Preparation Example 2, except that the molecular sieve was first soaked in a mixture formed by adding 12g of Cu2SO4 to 300g of KH2PO4 solution with a concentration of 15wt%, and then calcined once (600℃, 1h). After being mixed with aluminum sol and shaped, it was calcined a second time (650℃, 4h) to obtain catalyst Dβ-3.
[0090] Preparation of Comparative Example 6
[0091] The catalyst was prepared according to the literature "Research on one-step alkylation process for preparing mesitylene", and the Al2O3 supported V2O5-Cr2O3 catalyst was obtained and named D-4.
[0092] The acid content of the catalyst in the above preparation examples and comparative examples is shown in Table 1.
[0093] Table 1
[0094]
[0095]
[0096] Examples 1-8 and Comparative Examples 1-6 are used to illustrate the synthesis of mesitylene.
[0097] Example 1
[0098] In a fixed-bed reactor, catalyst Y-1 from Preparation Example 1 was used to react methanol and o-toluidine. The molar ratio of methanol to o-toluidine was 5.5:1, and the mass hourly space velocity (WHSV) of methanol and o-toluidine was 1 h⁻¹. -1 The reaction temperature is 440℃. The raw materials are pumped into the reactor using a raw material pump. o-Toluidine and methanol are vaporized in the reactor and react with the catalyst after contacting the catalyst bed.
[0099] Examples 2-7, Comparative Examples 1-6
[0100] The method of Example 1 was followed, except that the catalysts in Preparation Examples 2-7 and Comparative Examples 1-6 were used instead of the catalyst in Preparation Example 1, while other conditions remained unchanged.
[0101] Example 8
[0102] In a fixed-bed reactor, catalyst Y-1 from Preparation Example 1 was used to react methanol and o-toluidine. The molar ratio of methanol to o-toluidine was 2.5:1, and the mass hourly space velocity (WHSV) of methanol and o-toluidine was 1 h⁻¹. -1 The reaction temperature is 380℃. The raw materials are pumped into the reactor using a raw material pump. o-Toluidine and methanol are vaporized in the reactor and react with the catalyst after contacting the catalyst bed.
[0103] The results of the 10-hour test reaction of the above embodiments and comparative examples are shown in Table 2.
[0104] Table 2
[0105]
[0106] As shown in the table above, the catalyst provided by this invention is used to produce mesitylene, achieving green production of mesitylene, effectively reducing the selectivity of the main byproduct N,N-dimethylaniline, and improving the selectivity of the target product mesitylene while ensuring catalyst life.
[0107] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A method for producing mesitylenetrimethylaniline, wherein, The method includes: reacting o-toluidine and a methylating agent in the presence of a catalyst at a reaction temperature not lower than 380°C; The catalyst comprises a molecular sieve, an oxide binder, and a modifying component. The modifying component is loaded on both the molecular sieve and the oxide binder. The modifying component contains Cu and P. The percentage of the medium-strong acid in the catalyst is not less than 40% of the total acid content, and the percentage of the strong acid in the catalyst is not less than 30% of the total acid content. The percentage of the medium-strong acid in the total acid content is calculated as the percentage of the desorption peak area at 250℃-450℃ measured using the NH3 temperature-programmed desorption method to the total acid desorption peak area. The percentage of the strong acid in the total acid content is calculated as the percentage of the desorption peak area at 450℃-550℃ measured using the NH3 temperature-programmed desorption method to the total acid desorption peak area.
2. The method according to claim 1, wherein, The methylating agent is formic acid and / or methanol; And / or, the molar ratio of o-toluidine to the methylating agent is 2-20:1, preferably 2.5-8:
1.
3. The method according to claim 1 or 2, wherein, The reaction conditions include: a reaction temperature of 380-480℃, and a mass hourly space velocity (H₂S) of 0.1-5 h⁻¹ for the o-toluidine and the methylating agent. -1 ; Preferably, the reaction conditions include: a reaction temperature of 380-450°C, and a mass hourly space velocity (HHSV) of 0.1-2 h⁻¹ for the o-toluidine and the methylating agent. -1 ; Preferably, the reaction is a gas-phase reaction.
4. The method according to claim 1 or 2, wherein, The catalyst contains 42-47% medium-strong acid, and the percentage of medium-strong acid in the total acid is expressed as the percentage of the desorption peak area at 250℃-450℃ as measured by the NH3 temperature-programmed desorption method relative to the total acid desorption peak area. And / or, the percentage of strong acid in the catalyst is 30-36% of the total acid content, and the percentage of medium-strong acid in the catalyst is expressed as the percentage of the desorption peak area at 450℃-550℃ measured using the NH3 temperature-programmed desorption method relative to the total acid desorption peak area.
5. The method according to claim 1 or 2, wherein, The molecular sieve is selected from at least one of Y-type molecular sieve, ZSM-5 type molecular sieve, β-type molecular sieve, MCM-22 type molecular sieve and mordenite type molecular sieve, preferably at least one of Y-type molecular sieve, ZSM-5 type molecular sieve and β-type molecular sieve; And / or, the oxide binder is aluminum oxide and / or silicon oxide.
6. The method according to claim 1 or 2, wherein, In the catalyst, the Cu:P molar ratio is 1:0.1-10, preferably 1:0.2-0.5, wherein Cu is calculated as CuO and P is calculated as P2O5; And / or, the mass ratio of the molecular sieve to the oxide binder (calculated as oxide) is 95:5-20:80, preferably 85:15-60:40; And / or, the mass ratio of the oxide binder (calculated as oxide) to the copper (calculated as element) is 75:25-99:1, preferably 90:10-98:
2.
7. The method according to claim 1 or 2, wherein, The method for preparing the catalyst includes: (1) Mix the molecular sieve and oxide binder to obtain a mixture; (2) The mixture obtained in step (1) is mixed with a solution containing copper precursor and phosphorus compound and then calcined once.
8. The method according to claim 7, wherein, In step (1), the oxide binder is a solid oxide binder and / or a sol-gel oxide binder, preferably a sol-gel oxide binder; Preferably, the concentration of the sol-oxide binder is 0.1-50 wt%, more preferably 10-30 wt%; Preferably, the pH of the sol-gel oxide binder is 1-5; Preferably, the average particle size of the sol-gel oxide binder is 0.1-300 nm; And / or, in step (1), the silicon-aluminum molar ratio n(SiO2):n(Al2O3) of the molecular sieve is 2-1000:1, preferably 2-100:1; Preferably, in step (1), the average particle size of the molecular sieve is 0.01-50 μm, and more preferably 0.1-20 μm.
9. The method according to claim 7, wherein, In step (2), the copper precursor is selected from copper-soluble compounds, preferably from at least one of copper chloride, cuprous chloride, copper nitrate, copper sulfate and cuprous sulfate; And / or, in step (2), the phosphorus-containing compound is selected from at least one of phosphoric acid, phosphorous acid, soluble phosphate and phosphite; Preferably, the soluble phosphate is selected from at least one of ammonium phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate.
10. The method according to claim 8, wherein, Step (2) further includes: introducing a peptide solvent into a solution containing a copper precursor and a phosphorus-containing compound and mixing it with the mixture obtained in step (1) to form a mold; Preferably, the adhesive solvent is selected from at least one of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, formic acid, and acetic acid; Preferably, the amount of the adhesive solvent is such that the pH of the solution containing the copper precursor and the phosphorus-containing compound is 1-4.
11. The method according to claim 7, wherein, In step (2), the calcination conditions include: a temperature of 450-800℃ and a time of 1-15h; Preferably, in step (2), the calcination conditions include: a temperature of 500-700℃ and a time of 1-12h.